Short Chain Fatty Acids Modulate the Growth and Virulence of Pathosymbiont Escherichia coli and Host Response - Shiying Zhang; Belgin Dogan; Cindy Guo; Deepali Herlekar; Katrina Stewart; Ellen J. Scherl; Kenneth W. Simpson (MDPI AG, 2020)
Short chain fatty acids (SCFA), principally acetate, propionate, and butyrate, are produced by fermentation of dietary fibers by the gut microbiota. SCFA regulate the growth and virulence of enteric pathogens, such as enterohemorrhagic E. coli (EHEC), Klebsiella and Salmonella. We sought to investigate the impact of SCFA on growth and virulence of pathosymbiont E. coli associated with inflammatory bowel disease (IBD) and colorectal cancer (CRC), and their role in regulating host responses to bacterial infection in vitro. We found that under ileal conditions (pH = 7.4; 12 mM total SCFA), SCFA significantly (p < 0.05) potentiate the growth and motility of pathosymbiont E. coli. However, under colonic conditions (pH = 6.5; 65 to 123 mM total SCFA), SCFA significantly (p < 0.05) inhibit growth in a pH dependent fashion (up to 60%), and down-regulate virulence gene expression (e.g., fliC, fimH, htrA, chuA, pks). Functional analysis reveals that colonic SCFA significantly (p < 0.05) inhibit E. coli motility (up to 95%), infectivity (up to 60%), and type 1 fimbria-mediated agglutination (up to 50%). In addition, SCFA significantly (p < 0.05) inhibit the activation of NF-κB, and IL-8 production by epithelial cells. Our findings provide novel insights on the role of the regional chemical microenvironment in regulating the growth and virulence of pathosymbiont E. coli and opportunities for therapeutic intervention.